Controlled release of sulfasalazine release from "smart" pectin gel microspheres under physiological simulated fluids - Costas, Luciana (2012)
Sulfasalazine (SLZ) is a synthetic nonsteroidal anti-inflammatory drug used mainly for the treatment of an inflammatory bowel and other diseases. Two pectins with different methylation degrees were blended to synthesized gel microspheres by ionotropic gelation for SLZ encapsulation. The encapsulation efficiency was found to be around of 99% in all formulations tested. However, different SLZ release profiles related to the methylation degrees of pectin were observed. Mixture of low methylated (LM) and high methylated (HM) pectins in the presence of calcium(II) displayed the best microsphere morphologies among the formulations tested determined by optical and electronic microscopies. The percentage of drug release using a mixture of LM and HM pectins after 255 min in simulated gastric fluid (pH = 1.2), simulated intestinal fluid (pH = 6.8), and phosphate buffer (pH = 7.4) were 15.0%, 47.0%, and 52.2%, respectively.